(i) a^{4} – b^{4}

**Answer:** a^{4}-b^{4} = (a²+b²)(a²-b²)

(ii) p^{4} – 81

=(p²+9)(p²-9)

(iii) x^{4} – (y + z)^{4}

**Answer:** x^{4} – (y + z)^{4}

= (x²+(y+z) ²)(x²-(y+z) ²)

= (x²+(y+z)²)[(x+y+z)(x-y-z)]

(iv) x^{4} – (x – z)^{4}

**Answer:** x^{4} – (x – z)^{4}

=(x²-(x-z) ²)(x²+(x-z) ²)

=[(x+x-z)(x-x+z)](x²+(x-z) ²]

(v) a^{4} – 2a²b² + b^{4}

**Answer:** a^{4} – 2a^{2}b^{2} + b^{4}

This can be factorised by using the identity; (a - b)^{2} = a^{2} – 2ab + b^{2}

Factors = (a^{2} – b^{2})^{2} = (a^{2} – b^{2})(a^{2} – b^{2})